1069. In Vitro Activity of Tebipenem Against Clinically Significant Gram-Negative Bacteria Isolated from Patients with Cancer. (4th December 2021) - Gerges, Bahgat; Rosenblatt, Joel; Hachem, Ray Y; Raad, Issam I; Chaftari, Anne-Marie
Abstract: Background: Gram negative (GN) bacterial infections are on the rise in patients with cancer and frequently require extended hospital stays that may lead to a major increase in healthcare cost. This study aimed to evaluate the in vitro activity of a novel oral carbapenem, tebipenem against recent gram-negative clinical isolates from our cancer patients. Methods: All 173 clinical isolates from our cancer patients including 36 Extended Spectrum Beta-Lactamase (ESBL) isolates from blood cultures were tested against tebipenem and other comparators. Clinical and Laboratory Standards Institute (CLSI) approved broth microdilution method was used. Appropriate ATCC controls were included. MIC50, MIC90, MIC ranges and percent of susceptibility calculations ware made using FDA breakpoints when available. The tebipenem provisional susceptibility breakpoint for most GN organism is ≤ 0.125 mg/L. Results: Tebipenem and comparators antibiotics susceptibility percent (S: %), and MIC90 are shown in the table below. Tebipenem demonstrated highly potent activity against Escherichia coli, Klebsiella pneumoniae (including ESBL producing strains), Enterobacter cloacae and inhibited 90% of the Enterobacter aerogenes strains screened. MIC90 s ranged from 0.06-0.25 mg/L for all tested Enterobacteriaceae . At a provisional breakpoints of 0.125 mg/L, the susceptibilities, MICs and ranges were comparable to meropenem, and ertapenem. Comparative study between Tebipenem and comparators for MIC90 (mg/L.) and Susceptibility (%) results against Gram-Negative Bacteria Isolated from Patients with Cancer Conclusion: Our data demonstrate that oral tebipenem has promising activity against clinically significant bacterial pathogens isolated from cancer patients, and it has similar activity to that of other tested carbapenem. Further clinical evaluation for oral carbapenem treatment of bacterial infections is warranted. Disclosures: All Authors : No reported disclosures